2001
DOI: 10.1128/jvi.75.19.8957-8967.2001
|View full text |Cite
|
Sign up to set email alerts
|

Antigenically Distinct Conformations of CXCR4

Abstract: The major human immunodeficiency virus type 1 (HIV-1) coreceptors are the chemokine receptors CCR5 and CXCR4. The patterns of expression of the major coreceptors and their use by HIV-1 strains largely explain viral tropism at the level of entry. However, while virus infection is dependent upon the presence of CD4 and an appropriate coreceptor, it can be influenced by a number of factors, including receptor concentration, affinity between envelope gp120 and receptors, and potentially receptor conformation. Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
156
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(162 citation statements)
references
References 59 publications
3
156
3
Order By: Relevance
“…3E), this data suggests that any possible biomechanical effects of sulfatide on the cell membrane are unlikely to specifically induce up-regulation of CXCR4. CXCR4 exists in multiple conformational states, only some of which are recognized by the 12G5 antibody used here [37]. To exclude the possibility that sulfatide was inducing a conformational change on pre-existing surface CXCR4 receptors, cells were also transfected with CXCR4 tagged with HA and stained with anti-HA antibody.…”
Section: Discussionmentioning
confidence: 99%
“…3E), this data suggests that any possible biomechanical effects of sulfatide on the cell membrane are unlikely to specifically induce up-regulation of CXCR4. CXCR4 exists in multiple conformational states, only some of which are recognized by the 12G5 antibody used here [37]. To exclude the possibility that sulfatide was inducing a conformational change on pre-existing surface CXCR4 receptors, cells were also transfected with CXCR4 tagged with HA and stained with anti-HA antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Using a panel of mAbs to CXCR4, it was found that CXCR4 on both primary and transformed T, B and myeloid cells exhibited considerable conformational heterogeneity. 99 This conformational heterogeneity of CXCR4 explains the cell-type-dependent ability of CXCR4 antibodies to block chemotaxis to its ligand CXCL12. In addition, the mAb most commonly used to study CXCR4 expression, 12G5, recognizes only a sub-population of CXCR4 molecules on all primary cell types analyzed.…”
Section: Development Antibodies To Cxcr4mentioning
confidence: 99%
“…Moreover, gp120 and CXCL12 also differ in their regulation of specific cell cycle proteins involved in neuronal survival, namely p53, Rb, and E2F (Khan et al, 2003(Khan et al, , 2005, which are directly and indirectly modulated by AKT. This could depend on differences in the intrinsic efficacies of the two CXCR4 ligands (Khan et al, 2004) and/or the presence of multiple receptor conformations (Baribaud et al, 2001;Zhou et al, 2002). Furthermore, based on recent evidence suggesting that receptor internalization may regulate G protein-coupled receptor (GPCR)-mediated signaling in various ways (Lefkowitz and Shenoy, 2005), we hypothesized that gp120 and CXCL12 may also diverge in their ability to induce CXCR4 internalization.…”
Section: Introductionmentioning
confidence: 99%